ADHERENCE DETERMINANT ANALYSIS OF PLHIV ON ARV (ANTIRETROVIRAL) THERAPY IN SITUBONDO DISTRICT: Analisis Determinan Kepatuhan ODHA dalam Menjalani Terapi ARV (Antiretroviral) di Kabupaten Situbondo - Wulandari, Winda Cindy; Syafriadi, Mei; Riyanti, Rini; Sugih Utami, Wiwien; Rondhianto, Rondhianto (Universitas Airlangga, 2024)
Background: Human Immunodeficiency Virus (HIV) infection causes Acquired Immune Deficiency Syndrome (AIDS), a collection of symptoms arising from the deteriorating immunity. The number of people living with HIV worldwide continues to increase year-by-year. Those infected with HIV need antiretroviral (ARV) therapy to suppress the amount of HIV in the body. Purpose: This study aimed to investigate the determinants of adherence in people living with HIV/AIDS (PLHIV) undergoing ARV therapy in Situbondo Regency. Methods: This study employed a quantitative analytic observational approach with a cross-sectional design. Data analysis involved both descriptive and multivariate analysis. The population for this study consisted of 328 individuals, from which 212 were selected as samples, all being PLHIV on ART as of April 2022, sourced from ARV treatment services in Situbondo district. Results: The research analysis was based on predisposing factors, measured using three indicators: work, knowledge, and belief in ARVs. Supporting aspects were measured by two factors: ownership of health insurance and adherence counselling. Reinforcing factors were measured using two indicators: family support and stigma in the community. Conclusion: The study concluded that predisposing and reinforcing factors significantly influenced PLHIV adherence to antiretroviral therapy. However, supporting factors did not show a significant influence on adherence in PLHIV undergoing antiretroviral therapy in the Situbondo District.